Yearbook of the European Convention on Human Rights ; Annuaire de la Convention Europeenne des Droits de L'homme : The European Commission and European Court of Human Rights / Commission et Cour Europeennes des Droits de L'homme. - Council of Europe/Conseil de L'Europe.; SpringerLink (Online service) (Springer Netherlands : Imprint: Springer, 1961)
Foreword The The Committee Committee of of Ministers Ministers of of the the Council Council of of Europe Europe by by a a Re Re solution of 6th February I958, authorised the publication of a solution of 6th February I958, authorised the publication of a Yearbook Yearbook of of the the European European Convention Convention on on Human Human Rights. Rights. The The present present Volume Volume of of the the Yearbook Yearbook is is the the third third in in the the series. series. The The Yearbook, Yearbook, being being prepared prepared by by the the Directorate Directorate of of Human Human Rights of the Council of Europe, does not involve the responsibility Rights of the Council of Europe, does not involve the responsibility either either of of the the European European Commission Commission or or of of the the European European Court Court of of Human Human Rights. Rights. In In particular, particular, the the summaries summaries of of the the decisions decisions of of the Commission cannot be quoted against the actual texts of these the Commission cannot be quoted against the actual texts of these decisions. decisions.
Keywords: Humanities; Humanities / Arts; Humanities, general